Incidence of congenital anomalies in newborns born to mothers with heart disease - R. Y., Kalpana; S. J., Patil (International Journal of Contemporary Pediatrics, 2021)
Background: Heart disease is seen in 1% pregnancies. Prior studies have either looked at only the prevalence of congenital heart diseases (CHD) in newborns or the congenital anomalies (CA) in babies born to those with chronic medical disorders as a whole. There is only sparse literature looking specifically at their prevalence in mothers with heart disease. Methods: We aimed to study incidence of CAs in newborns born to mothers with heart disease and to study other relevant outcomes like prematurity, low birth weight and intrauterine growth retardation which have significant associations with CAs. The present study was a descriptive study consisting of retrospective and prospective data and consisted of pregnant women with heart disease from 2006 to 2010 and their newborns. Results: 55 pregnant women with their 55 newborns were selected. Among the 55 newborns, 15% babies had congenital anomalies including CHD, 13% had only CHDs. 21% babies with CHDs were born to CHD mothers and none of the mother baby diagnosis was completely concordant. No statistically significant outcome of CA in newborns born to mothers with heart disease was found. No statistically significant associations among low birth weight, prematurity and CAs was found. Conclusions: 15% had congenital anomalies including CHD. No statistically significant outcome of CA in newborns born to mothers with heart disease was found. Since the study population comprised of a small sample size, significant derivations could not be made. Further studies are required in this direction to see if associations are significant.